Estudio de alternativas para el diseño de un sistema de drenaje de la vía ubicada en la carrera 11 B entre las calles 7 y 8 Barrio Cundinamarca de Duitama Boyacá. - Tibaduiza Garcia, Oscar Javier (Universidad Antonio Nariño, 2022)
The roads are considered as spaces destined for the transit of people and vehicles, In addition to being the means of communication between one place and another, therefore, it is required that these meet the necessary factors of safety, comfort, efficiency and quality. The element that most jeopardizes these necessary characteristics on the roads, without Undoubtedly it is water, that is why some elements capable of mitigating the impact are determined negative hydraulic on the tracks. The uncovered roads are part of the largest road network in the country, and these are no strangers to this enemy, since they receive a lower budget for their design and maintenance, becoming the most abandoned by national administrations; on the There is currently no clear regulation that indicates the criteria for design, maintenance and construction for this type of roads.